Traditional methods of soaking or sprouting pulses reduce the flatulence causing raffinose family alpha-galactosides in regularly used nutritious edible legumes - Fahira Tasneem
Pulses are an alternative sustainable and inexpensive source of protein. They are rich in carbohydrates, proteins, vitamins, and minerals. The total soluble sugars in pulses include monosaccharides, disaccharides, and oligosaccharides. Legume seeds contain raffinose family oligosaccharides (RFOs) as their primary source of sugar reserves, which drive seed germination and improve seed vigor and longevity. The RFOs are also critical during plant growth and development in unfavorable environments. However, because monogastric animals, including humans, lack the enzyme alpha-galactosidase, they cannot digest the RFOs present in legume grains, leading to the accumulation of flatus due to microbial fermentation of RFOs in the large intestine. Subsequently, large amounts of carbon dioxide, methane, and hydrogen build up in the intestine due to flatulence. Flatulence, being induced by water-soluble RFOs, it is possible to reduce the levels of RFOs in the dietary pulses by traditional soaking of legumes. Herein, we report the RFOs levels of 21 common dietary pulses consumed in various forms, such as dry grains, soaked grains, and seed sprouts. We show that seed sprouts accumulate lower levels of RFOs compared to fresh vegetables. We hypothesize that the RFOs levels increase when the filled grains desiccate to mature and decrease when the desiccated seed commits to germination. Our study suggests incorporating highly nutritious pulses, such as sprouts, into diets to combat flatulence.